P055 Factors from human mesenteric adipose tissue control intestinal stem cell differentiation and proliferation in vitro. (21st January 2022) - Ziegler, J; Gerbeth, L; Brunkhorst, M F; Glauben, R; Weidinger, C; Siegmund, B
Abstract: Background: In Crohn's disease, hyperplastic mesenteric adipose tissue wrapping around inflamed small intestinal segments is a pathognomonic finding. Factors secreted by this so-called creeping fat can influence immune cells and affect disease severity in animal models. However, data on the interactions of adipose tissue and the intestinal epithelium are still sparse and derive almost exclusively from cell lines and animal models. Therefore, we employed primary human intestinal organoid culture and primary human adipose tissue explants to elucidate the role of adipose tissue-derived factors on the epithelium. Methods: Creeping fat and unaffected mesenteric adipose tissue from a Crohn's disease patient was used to produce adipose tissue-conditioned medium (ATcM). ATcM or control medium was added to growth medium (contains Wnt3a) and differentiation medium (Wnt3a removal) during primary human ileum-derived organoid culture. We analysed organoid morphology, proliferation, and phenotype by light microscopy, live cell imaging, resazurin viability assay, and reverse transcription quantitative polymerase chain reaction (RT-qPCR). Results: In the presence of ATcM, differentiation of organoids was accompanied by a subtle and only transient delay in the development of morphologic signs of differentiation, namely organoid budding and darkness. In line, RT-qPCR at day 4 showed high expression of the differentiation markers MUC2 and ALPI in ATcM as well as in control conditions. In stem cell-enhancing growth medium, however, ATcM from both unaffected mesenteric adipose tissue and creeping fat induced a profound alteration of organoid morphology, perfectly reflecting so-called spheroids. Additionally, this ATcM-treated organoids were larger than the control, which corresponded with increased proliferation as measured by resazurin assay. This stem-like phenotype was further confirmed by a reduced expression of the differentiation markers MUC2 and ALPI in ATcM-treated organoids compared to the control. Conclusion: Overall, our data suggest that factors from human mesenteric adipose tissue have profound effects on intestinal epithelial stem cells, while differentiated cells appear less affected. In the stem cell niche, they promote stem cell proliferation and inhibit differentiation. In Crohn's disease, factors released from creeping fat could thus play a significant role in the pathophysiology, e.g. by enhancing epithelial regeneration via a promotion of stem cell proliferation.